Determinants of stock market returns in Malaysia: evidence from FTSE KLCI / Muhammad Fadzli Kadir - Kadir, Muhammad Fadzli (Faculty of Business and Management, 2018)
The stock market was one of indicators in determining the future economy of a country. Bearish in the stock market refers to there is unfavourable signal to the economy while bullish in the stock market refers to there is positive outlook in future economy of a country. The trend of the major stock market index gives a perception to local and foreign direct portfolio investment towards a county and determining the determinants of stock market returns will help them in making investment decisions. This study highlighted the significant determinants in determining future movements of stock market returns in Malaysia. The quarterly time series data span over the period of the first quarter of 2008 to the first quarter of 2017 was used for this study.